Mechanical properties of composite parts manufactured in FDM technology. Issue 8 (18th October 2018) - Górski, Filip; Kuczko, Wiesław; Wichniarek, Radosław; Hamrol, Adam
Abstract : Purpose: This paper aims to study strength properties and accuracy of a new type of composites, in which matrix is manufactured additively, whereas infill is a polyurethane resin. The process of manufacturing these composites is invented and patented by authors. Design/methodology/approach: The authors developed a method of manufacturing composites, which was then used to build samples for tensile and bending tests (according to ISO 572 and ISO 178 standards), as well as measurements of accuracy. Findings: It was found that the method of composite manufacturing designed by the authors allows obtaining both stronger and cheaper parts in comparison with the traditional acrylonitrile butadiene styrene FDM parts. Research limitations/implications: The research was limited to static tests only, and no dynamic tests were performed on the manufactured samples. The accuracy analysis is only a basic one. Practical implications: Developed method allows to shorten the FDM process with simultaneous decrease of costs (in professional processes) and increase of strength of obtained products. Originality/value: Application of composite materials presented in the paper will significantly expand possibilities of using FDM method to manufacture functional, strong parts able to carry higher loads. Application of different combinations of thermoplastic matrix materials with different resin infills will allow to control properties of obtained composites. The solution is currently subject of a patent.